Evaluation of Lipid Profiles and Hematological Parameters in Hypertensive Patients - Hussain Farooq, Yousaf Ali, Aleema Ali, Mustafa Nadeem, Ghazanfar Ali Sirhindi, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the lipid profiles and hematological parameters in hypertensive patients. Study design: Cross sectional analytical study Place and duration of study: Department of Hematology, Shaikh Zayed Hospital, Lahore from 1st July 2021 to 31st December 2021. Methodology: Eighty hypertensive patients within the age group of 25-65 years were enrolled. A 5-cc blood was withdrawn from each study patient for analysis of their complete lipid profile including triglycerides, cholesterol, low density lipoproteins, high density lipoproteins as well as for hematological parameters analysis which included red blood cells, white blood cells hematocrits, hemoglobin, red blood cell indices and platelets. Result: The mean age of the patients was 51.89±12.47 years. There were 45 males and 35 females in this study. Obesity was more common in hypertensive women than men. Lipid profile except high density lipoproteins was significantly higher in patients with uncontrolled blood pressure levels. High red blood cells were observed in both males and females with uncontrolled blood pressure while the platelets level decreased in uncontrolled BP males and increased in uncontrolled BP females in comparison to controlled males and females respectively. An increased level of hemoglobin and hematocrit in patients from both genders with uncontrolled blood pressure was observed. Conclusion: Disturbed lipid profile and hematological parameters imbalances are related with the hypertension Key words: Lipid profile, Hematological parameters, Hypertension